Epidemiological Situation on Tick-Borne Borreliosis in the Russian Federation in 2019 Compared to the Period of 2002–2018 - S. A. Rudakova; N. A. Pen’evskaya; A. I. Blokh; D. A. Savel’ev; O. E. Teslova; N. E. Kaneshova; N. V. Rudakov; D. V. Trankvilevsky (Проблемы особо опасных инфекций, 2020)
Objective: to analyze the epidemiological situation on Ixodidae tick-borne borreliosis in the Russian Federation in 2019 in comparison with the period of 2002–2018.Materials and methods. The paper uses the data contained in Form No. 2 of the state statistical reporting for 2002–2019 and information obtained by the Reference Center for Monitoring Borreliosis of the Omsk Research Institute of Natural Focal Infections from 74 constituent entities of Russia in 2019. The main research method is epidemiological one with the use of modern information technologies.Results and discussion. In Russia, 8048 cases of tick-borne borreliosis (Lyme disease – LD) were recorded (5.48 0/0000) in 2019. The actual indicators of the LD incidence for the whole country and federal districts (FD) in 2019 were within the confidence limits predicted with linear regression based on the study of the dynamics of the epidemic process in 2002–2018 in the vast majority of cases. A steady upward trend in the LD incidence was observed during 2002–2019 in the Central Federal District due to 10 out of 18 entities (Moscow, Belgorod, Lipetsk, Moscow, Bryansk, Voronezh, Kursk, Ryazan, Tambov, Tula regions); in the Southern Federal District because of the Krasnodar Territory and the Volgograd Region; in the North Caucasus Federal District – because of the Stavropol Territory. Despite the fact that a downward trend in the incidence of LD has been established over the past 18 years in the North-West, Volga and Ural Federal Districts, in some subjects of these regions a trend towards an aggravation of the epidemiological situation is observed (the Komi Republic and Chuvashia, Penza Region). In the absence of a pronounced tendency to change in the incidence rate of LD in the Siberian and Far Eastern Federal Districts, Kemerovo Region-Kuzbass, the Republic of Tuva and the Trans-Baikal Territory where a growing trend has been identified require special attention. In the Ural and Siberian Federal Districts, the share of non-erythema forms among laboratory-confirmed cases of LD was higher than in other regions, which merits further study of the genome-specific features of borrelia populations and their carriers. Effective control of the LD epidemiological situation in Russia is possible provided that the control is improved and maintained, and the capacity of preventive measures and zoological-entomological monitoring of the activity and structure of the natural foci of LD is enhanced in the entities with the long-term tendency towards increase in the incidence of the disease.